Puerarin attenuates cisplatin-induced rat nephrotoxicity: The involvement of TLR4/NF-κB signaling pathway. - Xu Ma; Lei Yan; Qing Zhu; Fengmin Shao (PLoS ONE)
Puerarin was a major isoflavonoid derived from the Chinese medical herb radix puerariae (Gegen). In present study effect of puerarin on cisplatin nephrotoxicity was evaluated. Rat model of nephrotoxicity was established by a single intraperitoneal injection of cisplatin (7mg/kg). Puerarin was administrated through caudal vein injection once per day at the dose of 10mg/kg, 30mg/kg and 50mg/kg. Biochemical assays showed that after cisplatin treatment the serum urea and creatinine increased significantly compared with control (P<0.05). Cisplatin treatment significantly increased xanthine oxidase (XO) activity and malondialdehyde (MDA) formation, and significantly decreased the levels and /or activities of enzymatic and non-enzymatic antioxidants (GSH, GPx, GST, GR, SOD, CAT), in the kidney tissues. Renal levels of TNF-α and IL-6, two important inflammatory cytokines, were also upregulated by cisplatin. Histopathological examination indicated that cisplatin treatment resulted in severe necrosis and degeneration, hyaline casts in the tubules, intertubular hemorrhage, congestion and swelling in glomerulus and leukocytes infiltration in the kidney tissues. Western blot results demonstrated that cisplatin increased TLR4 and NF-κB protein expression in the kidney tissues. However, all these changes induced by cisplatin were significantly attenuated by puerarin treatment in dose-dependent manner, which indicated the renal protective effect of puerarin. Cell culture experiments illustrated that puerarin alone treatment concentration-dependently inhibited COLO205 and HeLa tumor cell growth and dose-dependently promoted the antitumor activity of cisplatin in COLO205 and HeLa tumor cells. The promotion effects might be attributed to suppression of cisplatin-increased NF-κB p65 expression by puerarin. Taken together, findings in this study suggested that puerarin exhibited renal protection against cisplatin nephrotoxicity via inhibiting TLR4/NF-κB signaling, with no inhibition but promotion effect on the antitumor activity of cisplatin. Puerarin might be a promising adjuvant agent for cisplatin chemotherapy.